Keragaman Gender Pengurus, Pengawas, dan Kinerja Koperasi di Indonesia - Jannah, Era Miftakhul; Risfandy, Tastaftiyan (Accounting Study Program, Faculty Economics and Business, Universitas Sebelas Maret, 2023)
This research aims to investigate the role of gender diversity in the management board and supervisory board on the performance of cooperatives in Indonesia. This study utilizes financial report data from 5,841 cooperatives in 2019, obtained from the 2020 BPS survey and selected based on several criteria by the researchers. The results of the analysis in this article indicate that board diversity has a positive influence on cooperative performance, as proxied by asset profitability and equity profitability. However, this study found empirical evidence indicating that diversity in the supervisory board does not have any significant impact on performance. The results of this study emphasize that the role of gender diversity in cooperative performance depends on the position of women within the cooperative, whether they are in managerial or supervisory roles. Penelitian ini bertujuan untuk menginvestigasi bagaimana keragaman gender di dewan pengurus dan pengawas memiliki peran pada kinerja koperasi di Indonesia. Penelitian ini menggunakan data laporan keuangan tahun 2019 dari 5.841 koperasi yang bersumber dari survei BPS tahun 2020 dan telah diseleksi berdasarkan beberapa kriteria dari peneliti. Hasil analisis di dalam artikel ini menunjukkan bahwa keragaman pengurus berpengaruh positif terhadap kinerja koperasi yang diproksi dengan rentabilitas aset dan rentabilitas modal sendiri. Akan tetapi, penelitian ini menemukan bukti empiris yang menunjukkan bahwa keragaman pengawas tidak memberikan pengaruh apapun pada kinerja. Hasil penelitian ini memberikan penekanan bahwa peran keragaman gender pada kinerja koperasi tergantung dari posisi perempuan di dalam koperasi tersebut, apakah menjadi pengurus atau pengawas.